PERILAKU PERAWAT DALAM MEMBUANG LIMBAH MEDIS DI RSUD dr. SAYIDIMAN MAGETAN TAHUN 2014 - Vina Septi Andriyani; Sri Poerwati; Handoyo . (Poltekkes Kemenkes Surabaya, 2015)
Medical wastes need to be handled properly. The forefront of this efforts is the waste generationnode. The health worker who are responsible for waste generation are nurses at the nursingwards. The the nurses were in the forefront and determine the fate of the medical waste treatmentin a hospital. The purpose of this study is to reveal nurses’ behavior pertaining to the managementof medical waste.Data were collected through interviews and observation of the behavior of the nurses on themorning duty, than analyzed the data descriptively.Results showed that 64% of waste generation location has made efforts in the sorting of wastes,but all of them (100%) has not been doing well in stowage. It is not easy to understand, since75% of the nurses have good knowledge, but only 54% who carry out the disposal of medicalwaste properly. Therefore it is advisable to provide support to medical waste disposal facilities throughout the waste generating rooms and implementing reward and punishment system for those who should do so.